BEFORE INSURANCE: A CASE FOR THE EMBEDMENT OF NON-PROBABILISTIC TRADITIONAL RISK MANAGEMENT (TRM) PRACTICES IN DISASTER PRONE ENVIRONMENT - Akpan, Sunday Sunday (PEOPLE: International Journal of Social Sciences, 2015)
This paper focuses on a priori risk management alternatives open to individuals and organizations, especially small business organizations (SBOs) in emerging communities. It is an examination of the various TRM practices considered to be non-probabilistic. It proposes a natural way of managing risk prior to considering conventional and contractual risk management method like insurance, especially where it is expensive and probably unaffordable. The emergent of natural disasters at homes, workplaces and habitable environments and the attendant and almost unmitigated loss exposure through insurance system has called for this investigation. And because insurance is just one method of managing risk, there is need to explore other complementary methods that may not necessarily involve the intrigues of probability calculations, premium payment and claim administration. Being a conceptual paper, the method of inquiry is basically a review of extant literature with intensive archival and document readership (ADR).The various TRM loss-related areas examined include property, liability, personnel and non-income loss exposures. The TRM practices found to be useful in managing these loss exposures include parameter fencing, intangible heritage, control of urban sprawling, preserving traditional mud-brick and timber-laced dwellings, cross training, succession planning, drainage surveillance and good land use and forest conservation etc. In conclusion, these practices are natural ways of preventing the occurrence of undesired event and does not provide for probabilistic calculations and prediction of uncertain future events. Now that catastrophic risk occurrence has assumed a new dimension, TRM constitute a priori expected risk management framework for managing risk by individuals and organizations while thinking about conventional insurance in emerging communities.